2020
DOI: 10.1002/pits.22415
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting 12th‐grade students' physics achievement

Abstract: The current study aimed to determine and predict 12th-grade students' physics achievement in terms of some selected cognitive, physics-related effective, personal, and socioeconomic characteristics in Turkey. Four hundred and ninety-six students (273 female and 223 male) from 18 high schools formed the study group. Findings indicated that cognitive characteristics including science achievement and physics course grades explained the largest amount of variance (60.6%) in the achievement by itself. Physics inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
0
4
0
4
Order By: Relevance
“…Conceptual knowledge is elaborated as the understanding and comprehension of ideas, principles, and theories etc. which are abstract in nature and may not have any physical occurrences (Taslidere, 2020). The academic achievement is defined as gain of higher scores/grades and performing skillfully for the solution of any given problem (Wider, & Wider, 2023).…”
Section: Research Problemmentioning
confidence: 99%
“…Conceptual knowledge is elaborated as the understanding and comprehension of ideas, principles, and theories etc. which are abstract in nature and may not have any physical occurrences (Taslidere, 2020). The academic achievement is defined as gain of higher scores/grades and performing skillfully for the solution of any given problem (Wider, & Wider, 2023).…”
Section: Research Problemmentioning
confidence: 99%
“…The number of studies investigating the individual and collective effects of the student, family and school-related factors on achievement is limited (Engin-Demir, 2009;Güvendir, 2014;Ölçüoğlu & Çetin, 2016;Önder & Uyar, 2018;Sarı et al, 2017;Taslidere, 2020) and none of them have studied the collective effects of aforementioned factors on math achievement according to the location of the school in Turkey. Hence, this study aimed to determine how well each set of the student, family and school-related factors predict 4th grade students' math achievement over and above the other(s) in schools located within different regions in Turkey.…”
Section: Purpose Of the Researchmentioning
confidence: 99%
“…The independent variables were selected based on theoretical and empirical findings from previous research. Besides, the data availability, comparability, criticality and whether or not it will enable comprehensive evaluation were also taken into consideration (Ataç, 2019;Engin-Demir, 2009;Farooq et al, 2011;Ker, 2016;Kraft & Dougherty, 2013;Mohammadpour, 2013;OECD, 2019;Özer & Anıl, 2011;Semeraro et al, 2020;Şirin, 2005;Takashiro, 2017;Taslidere, 2020). The data concerning the student and family-related variables were derived from the student's questionnaire and those of the school-related variables were obtained from school principal's questionnaire.…”
Section: Variablesmentioning
confidence: 99%
“…In the literature, it is discussed that gender is one of the critical factors that affects students' achievement in science education. Some studies found it as the significant predictor (Mcpanang, 2016;Taslidere, 2020) and the others (Awodun, Oni, & Aladejana, 2014;Yerdelen-Damar & Peşman, 2013) found it as insignificant predictor for the science achievement. Likewise, some of the previous studies (Ates, 2005;Chambers & Andre, 1997;Kibirige & Tsamago, 2019) reported insignificant, and the others (Chu, Treagust, & Chandrasegaran, 2009;Wang & Andre, 1991) found significant interactions between gender and treatments.…”
Section: Simulationmentioning
confidence: 99%